1985
DOI: 10.1111/j.1476-5381.1985.tb09454.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combination of metoprolol and dazmegrel on myocardial infarct size in rats

Abstract: 1 The effects ofacute pretreatment with metoprolol, dazmegrel and a combination of these two drugs has been examined on myocardial infarct size in rats. Ischaemic damage was assessed 4 h after coronary artery occlusion in anaesthetized rats and after 48 h of ischaemia in conscious rats. Infarct size was measured histochemically (by using periodic-acid-Schiff diastase reaction for glycogen) and by standard histological examination (haematoxylin and eosin stain). 2 There was some evidence of protection of the my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is possible that in the latter case, a 6‐h ischemia was too long. In a study performed in rats with CAO (4 and 48 h), it was shown that metoprolol (2 mg/kg) reduces the IS/LV ratio at a 4‐h occlusion by 50% but does not affect infarct size at a 48‐h CAO [54]. It is possible metoprolol delays the onset of ischemic necrosis but does not prevent it.…”
Section: The Cardioprotective Effect Of β‐Ar Antagonistsmentioning
confidence: 99%
“…It is possible that in the latter case, a 6‐h ischemia was too long. In a study performed in rats with CAO (4 and 48 h), it was shown that metoprolol (2 mg/kg) reduces the IS/LV ratio at a 4‐h occlusion by 50% but does not affect infarct size at a 48‐h CAO [54]. It is possible metoprolol delays the onset of ischemic necrosis but does not prevent it.…”
Section: The Cardioprotective Effect Of β‐Ar Antagonistsmentioning
confidence: 99%